PENGARUH BIMBINGAN BELAJAR DAN PEMANFAATAN INTERNET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS VII SMP NEGERI 2 KOTA JAMBI - Meuthia, Rembulan Putri; Afrila, Diliza (Universitas Batanghari Jambi, 2021)
AbstractThis study aims to determine (1) the effect of tutoring on student learning outcomes in social studies subjects in class VI SMP Negeri 2 Jambi City, (2) the influence of internet use on student learning outcomes in social studies subjects in class VII SMP Negeri 2 Jambi City, (3) the effect of tutoring and the use of the internet on student learning outcomes in social studies subjects in class VII SMP Negeri 2 Jambi City. This type of research is a survey method research with two independent variables and one dependent variable. The total population in this study was 130 people. The sampling technique used in this study was proportional random sampling, so that 98 people were selected as research samples. The technique of collecting data in this research is by distributing questionnaires via google form to research respondents. The data analysis technique in this study was multiple regression with the SPSS for Windows Version 21 program. The results showed that (1) the effect of tutoring on learning outcomes obtained a value of tcount > ttable (6.038 > 1.984). That is, tutoring has a significant effect on student learning outcomes in social studies subjects in class VII SMP Negeri 2 Jambi City, (2) The effect of internet use on learning outcomes is obtained by the value of tcount> ttable (5.580>1.984). That is, learning facilities have a significant effect on student learning outcomes in social studies subjects in class VII SMP Negeri 2 Jambi City, and (3) tutoring and internet use significantly affect student learning outcomes on social studies subjects in class VII SMP Negeri 2 Kota Jambi. This is based on Fcount > Ftable (26.827 > 0.09), so it can be concluded that H0 is rejected.Keywords: Tutoring, Internet, Learning Outcomes